Transfer doświadczeń międzynarodowych z zakresu rozwoju przedsiębiorczości na Dolnym Śląsku na przykładzie agencji rozwoju regionalnego - Adamczuk, Franciszek (Transfer of International Experiences in Entrepreneurship Development in Lower Silesia - the Regional Development Agency, 2008)
The paper aims to present problems connected to transferring experiences in the field of entrereneurship development in the international format. A case study of one of Lower Silesia most proactive entities - the Regional Development Agency- has been presented. In Lower Silesia case, business-surrounding entities (as RDA) are responsible for number of such transfers. They develop international relations and take part in local and regional entrepreneurship development by transferring some of other EU countries experiences. The paper ends with the assessment of RDA role in transferring the entrepreneurship experiences and with the conclusions that can substantiate business-surrounding entities position in the international and regional market.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 12, s. 11-19